SCHIZOAFFECTIVE DISORDER AS AN IDEA FOR ILLUSTRATION - Megatirta, Taffana; Roslan, Nur Fatiyah Binti (Eduarts: Jurnal Pendidikan Seni, 2025)
Mental health is a crucial aspect that needs to be given equal consideration as physical health. By prioritizing both, one can effectively prevent the onset of diseases that may negatively impact daily activities. However, the prevalence of stigma and lack of understanding regarding mental disorders in society can have detrimental consequences for those affected. As a schizoaffective disorder sufferer, the author aims to convey personal experiences and feelings about the condition through illustrations. The illustrations' titles are derived from the symptoms of schizoaffective disorder personally encountered by the author. The "A Beautiful Mind" zine contains illustrations and a narrative description of schizoaffective disorder, offering insight into the condition from the author's perspective. The audience is expected to gain informative knowledge about mental disorders, particularly schizoaffective disorder through the author's experiences and insights as a sufferer.